Answer :

Given … (1)


And


… (2)


Expressing x of equation (1) in terms of y,






… (3)


Substituting (3) in (2),







6 (10y + 5) = 35 (2y)


60y + 30 = 70y


30 = 70y – 60y


30 = 10y


y = 30/ 10


y = 3


Substituting y value in (3),





x = 2


By solving, we get x = 2 and y = 3.


Justification:


(1) -



1 + 1 = 2


2 = 2


And (2) -





We can see that x = 2 and y = 3 satisfy equations (1) and (2).


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Let us solvWest Bengal Mathematics

Let us solvWest Bengal Mathematics

Let us write the West Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us draw the gWest Bengal Mathematics

Let us form the sWest Bengal Mathematics

Let us express thWest Bengal Mathematics

Let us solvWest Bengal Mathematics